Noise and distortion figure: an extension of noise figure definition for nonlinear devices - Lavrador, P.M.
This paper deals in the integration of additive and nonlinear distortion noise contributions into a single new figure of merit: Noise and Distortion Figure, NDF. In the same way as traditional noise figure, NF, was conceived to be a measure of SNR degradation, NDF is now proposed as its extension to nonlinear systems, as a measure of SINAD degradation. NDF definition is discussed and its application to SINAD evaluations in systems of practical interest to the wireless community is exemplified.